A Chemogenetic Approach for the Optical Monitoring of Voltage in Neurons. (25th January 2019) - Sundukova, Mayya; Prifti, Efthymia; Bucci, Annalisa; Kirillova, Kseniia; Serrao, Joana; Reymond, Luc; Umebayashi, Miwa; Hovius, Ruud; Riezman, Howard; Johnsson, Kai; Heppenstall, Paul A.
Abstract: Optical monitoring of neuronal voltage using fluorescent indicators is a powerful approach for the interrogation of the cellular and molecular logic of the nervous system. Herein, a semisynthetic tethered voltage indicator (STeVI1) based upon nile red is described that displays voltage sensitivity when genetically targeted to neuronal membranes. This environmentally sensitive probe allows for wash‐free imaging and faithfully detects supra‐ and sub‐threshold activity in neurons. Abstract : Spannungsprüfer : Ein semisynthetisch gebundener Spannungsindikator (STeVI1) auf der Basis von Nilrot wurde entwickelt, der nach Gentransport in Nervenzellmembranen Spannungssensitivität zeigt. Die umgebungssensitive Sonde ermöglicht die Bildgebung ohne Waschschritte und detektiert über‐ und unterschwellige Aktivität in Nervenzellen.